Propensity score analysis revisited - Hashimoto, Yohei; Yasunaga, Hideo (Annals of Clinical Epidemiology, 2025)
Propensity score (PS) is the probability of the exposure being assigned, conditional on the observed baseline covariates. Many observational studies have used PS analyses to investigate the effects of exposure on outcomes. This report reviews the five steps of PS analyses: 1) calculating PS; 2) checking the overlap of PS; 3) implementing a matching or weighting method including PS matching, inverse-probability-of-treatment weighting, standardized mortality ratio weighting, matching weighting, and overlap weighting; 4) diagnosing the covariate balance; and 5) comparing the outcomes. Two groups are often compared in PS analyses; however, three-group comparisons can provide clinicians with more benefits in many situations in routine clinical practice. Thus, we describe not only two-group comparisons but also three-group comparisons by introducing a few studies that used generalized PS to compare three groups.